Macro-/nanoporous Al-doped ZnO/cellulose composites based on tunable cellulose fiber sizes for enhancing photocatalytic properties. (15th December 2020) - Li, Hongwei; Zhang, Lili; Lu, Hailong; Ma, Jinxia; Zhou, Xiaofan; Wang, Zhiguo; Yi, Caifu
Highlights: Porous Al-doped ZnO/cellulose composites (AZOC) were prepared. The size of macro/nano cellulose fibers affected the structure of AZOC composite. The AZOC composite exhibited the highly photocatalytic activity. The AZOC composite possessed excellent recyclability. Abstract: Porous Al-doped ZnO/cellulose (AZOC) composites were successfully fabricated via a chemical deposition method. The micro-/nano cellulose fibers (MNCF) with tunable sizes were prepared by grinding treatment, and used as substrates for synthesizing ZnO/MNCF and AZOC composites. With the increasing of grinding treatment times, the average fiber diameter of MNCF decreased, that of MNCF-10, MNCF-20 and MNCF-30 were 100 nm, 58 nm and 31 nm, which was observed by scanning electron microscopy (SEM). The fiber sizes of MNCF played an important role in the sizes of ZnO and Al-doped ZnO, also pore structures and photocatalytic properties of ZnO/MNCF and AZOC composites. The sizes of ZnO (or Al-doped ZnO) nanoparticles decreased with the decreasing of MNCF diameter. The AZOC composite with average fiber diameter of 31 nm (under grinding treatment of 30 times) exhibited the highest porosity (94.6 %). The obtained ZnO/MNCF and AZOC composites were further analyzed using X-ray diffraction (XRD), Raman spectrometry, X-ray photoelectron spectroscopy (XPS), and UV–vis diffuse reflectance spectroscopy (DRS). Due to the introduction of Al element dopant, the AZOC showed a much better photocatalytic efficiency (89.9 %) than pure ZnO powders (22.5 %) and ZnO/MNCF composites (53.3 %). Moreover, the AZOC composite can be recycled more than 10 times with negligible photocatalytic efficiency loss.